PENGARUH PERSEPSI PELANGGAN TERKAIT IMPLEMENTASI PRINSIP ETIKA BISNIS ISLAM TERHADAP LOYALITAS PELANGGAN DALAM MELAKUKAN TRANSAKSI E-COMMERCE SHOPEE DI SURABAYA - Zafira, Amara Rida; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2024)
E-Commerce Shopee plays an important role in making it easier for people to fulfill their needs and desires in buying and selling. This study aims to assess the impact of customer perceptions on the implementation of Islamic business ethics principles on customer loyalty in e-commerce transactions at Shopee Surabaya. The research method used is quantitative by involving 100 respondents as a sample. The questionnaire was distributed through Google Form using a Likert scale to measure customer perceptions related to the implementation of Islamic business ethics principles and their impact on customer loyalty. The results showed that the variable of customer perception related to the implementation of Islamic business ethics principles had a positive effect on customer loyalty in conducting Shopee e-commerce transactions in Surabaya. However, it does not have a full effect, which is an effect of 35.4%. This study provides managerial implications for Shopee companies to better understand the principles of Islamic business ethics and implement them in the transaction process, to create and encourage an attitude of loyalty in consumers and will increase sales in Shopee e-commerce due to an attitude of customer loyalty.